Spatial structure effects on fisheries management for Lake Victoria's Nile Perch / Santiago Gómez-Cardona - Santiago Gomez (University of Heidelberg, Department of Economics, 2022)
Lake Victoria, globally the second-largest freshwater Lake by surface area, houses an artisanal Nile Perch Fishery that directly involves around 200K people. While the 10 whole Lake surface is potentially available to fishing activities, the fishing vessels' operational and technical characteristics, in conjunction with fuel costs, create stark differences in the access costs between areas close to the shore and those farther away (up to 70Km from the nearest dry land). Evidence indicates that most fishing effort is made very close to the shore. There is an imbalance between the fish stock 15 distribution and the fishing fleet's ability to access and profit from it. Nonetheless, this aspect has not been considered in the literature, not in its consequences nor in the way it can be leveraged for management purposes. This paper employs a model replicating Nile Perch Fishery's most critical spatial aspects. It explores the potential of a Policy declaring the central areas of the Lake as Reserve areas. While 20 not a first-best Policy, it reduces the costs in patrolling activities, benefiting and levering the higher costs of reaching reserved areas. It reduces the variance in the system as it is perturbed by external factors, e.g., prices, and hence, it increases its resilience to external shocks.
urn:nbn:de:bsz:16-heidok-313425
Keywords: O13; Q22; Q28; 330; spatial effort distribution; natural resource management; management strategies; reserve areas; fisheries